THE FACTORS THAT INFLUENCE THE INCIDENCE OF DOMESTIC VIOLENCE IN WOMEN AT KABUPATEN TANAH BUMBU : FAKTOR YANG MEMPENGARUHI KEJADIAN KEKERASAN DALAM RUMAH TANGGA (KDRT) PADA WANITA DI KABUPATEN TANAH BUMBU - Udiyani, Ritna; Dewy, Tika Sari; Rahmadita, Eka Erni (WELL BEING, 2025)
Domestic violence is a behaviour that causes physical, sexual, psychological suffering and neglect of the household. The aim of this study to determine what factors influence the incidence of domestic violence in women. This type of study was Analytical with a Cross-sectional approach, the sample in this study were 384 respondents with the Quota Sampling technique. The instrument was used a questionnaire. The results of the study obtained with a value (p value <0.05) namely the factors of wife's age, wife's education, social environment and third party intervention with the hypothesis H1 was accepted, with a value (p value> 0.05) namely the economic factor with the hypothesis H0 was accepted. Multivariate results obtained on the wife's education factor having a value of 17.87 times higher risk. The conclusion of the study was that the most influential factor on the incidence of domestic violence in women was the wife's education factor with an OR value of 17.87 times more at risk of experiencing domestic violence.